2015
DOI: 10.5721/eujrs20154807
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Ground Control Points for Geometric Correction Using Genetic Algorithm with Global Accuracy

Abstract: Establishing the ground control point (GCP) network is a pre-requisite for georeferencing raw image data. Given current typical digital spatial database quality, much interest among users is about the accuracy of the geometric correction model that yields the final product. This paper reports an approach to optimizing GCP assembly using a genetic/evolution algorithm. The paper also suggests an optimal criterion for accuracy assessment through appraisal of global accuracy of the transformation, which is compute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(14 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…The accuracy of the three above mentioned maps, produced in this research (two that determined the water body and one that reported the land cover data for the entire water basin) was calculated according to the confusion matrix (Story & Congalton, 1986). The realization of the matrix made it possible to verify the real correspondence of the randomly distributed control points for each investigated class of land cover (Nguyen, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…The accuracy of the three above mentioned maps, produced in this research (two that determined the water body and one that reported the land cover data for the entire water basin) was calculated according to the confusion matrix (Story & Congalton, 1986). The realization of the matrix made it possible to verify the real correspondence of the randomly distributed control points for each investigated class of land cover (Nguyen, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…The purpose of the GC is to correct the deformations that occur during imaging [ 30 ]. GC methods are divided into parametric and non-parametric models [ 31 ].…”
Section: Preprocessing Methodsmentioning
confidence: 99%
“…The required number of GCPs, their spatial distribution and their accuracy are the most important issues in selecting GCPs for accuracy assessment of DEMs (Höhle and Höhle 2009). General guideline for the number of GCPs is that they must be large enough and uniformly distributed all over the test area to obtain reliable accuracy measures (Nguyen 2015;Oniga et al 2018). In this paper, we rely on this general guideline about the necessity of uniformly distributed GCPs and proposed and justified equation 1 to calculate required number of GCPs using a defined confidence interval for RMSE.…”
Section: Required Number Of Gcpsmentioning
confidence: 99%
“…Some researchers performed the accuracy assessment of GDEMs globally (Rodriguez et al 2006) while some others investigated their accuracy in a local area (Rexer and Hirt 2014;Zhao et al 2011). However, the optimum number of Ground Control Points (GCPs) has been always a concern for evaluating the accuracy of spatial data such as georeferenced images (Nguyen 2015;Oniga et al 2018), and DEMs (Höhle and Höhle 2009). Accordingly, in this paper an innovative method is proposed to determine the required number of GCPs for assessing the accuracy of DEMs.…”
Section: Introductionmentioning
confidence: 99%